Właściwości nasion a cechy morfologiczne siewek sosny zwyczajnej (Pinus sylvestris L.) - Buraczyk, Włodzimierz (Leśne Prace Badawcze, 2010)
Samples of Scots pine seeds from three sources were used for the laboratory investigation: managed seed stands (GDN), seed stands excluded from harvesting (WDN) and a seed plantation. Seeds were X-rayed prior to commencement of the laboratory investigation, which made it possible to determine embryo and megagematophyte sizes. Those seeds produced seedlings which did not differ significantly one from another in terms of morphological characteristics either in the field or in the laboratory. A regression analysis revealed a close relationship between seed characteristics (seed weight, embryo and megagematophyte sizes) and the size of seedlings reared from them. A detailed analysis indicated that seedlings reared from seeds weighing up to 6 mg were significantly smaller than those reared from heavier seeds. That applies both to the aboveground seedling parts and the root system that was two or three times smaller in pines reared from low-weight (up to 6 mg) than that in seedlings reared from heavier seeds. Root systems of seedlings reared from seeds weighing up to 4 mg on the average formed 68 apical domes, whereas root systems grown from seedlings weighing over 9 mg had approximately 170 apical domes. The above relationships apply to seeds originating from all the three sources under analysis.